Developing a leadership cadre for the 21st century: a case study of management development in the UK's new civil service - Hockey, Julia; Kakabadse, Nada K.; Kakabadse, Andrew P. (2005)
he UK civil service has experienced considerable challenges in introducing new ways of working as well as alternative organizational designs, both for the purposes of achieving `best value' during the last two decades of the last century. In addition to the strategic changes introduced, people development and training has been equally vigorously pursued in order to facilitate the reconfigurations that have been implemented. This article presents the findings of a study exploring how extensive development and training strategies are assisting managers to confront and address the challenges they face better, now and into the future. A mixed picture emerges principally highlighting the challenges of aligning human resource management (HRM) strategy with organizational strategy within a devolved organizational civil service configuration. - Reproduced.
Keywords: Leadership - Great Britainp; Management - Great Britain; Civil service - Great Britain; Civil service